Gastric GISTs: Analysis of c-Kit, PDGFRA and BRAF mutations in relation to prognosis and clinical pathological characteristics of patients – A GIRCG study. Issue 8 (August 2016) - Capelli, L.; Petracci, E.; Quagliuolo, V.; Saragoni, L.; Colombo, P.; Morgagni, P.; Calistri, D.; Tomezzoli, A.; Di Cosmo, M.; Roviello, F.; Vindigni, C.; Coniglio, A.; et al.
Abstract: Background: Gastric gastrointestinal stromal tumors (GISTs) represent a subgroup of GISTs with a better prognosis than those located in other areas. In this retrospective study we performed a molecular characterization of a large series of patients with gastric GISTs in relation to clinical–pathological characteristics and prognosis. Methods: DNA was extracted from paraffin-embedded sections from 221 gastric GIST patients submitted to surgery. Exons 9, 11, 13 and 17 of KIT, exons 12 and 18 of PDGFRA and exons 11 and 15 of BRAF were analyzed by direct sequencing. Cox regression analysis adjusted for clinical–pathological factors was performed to evaluate KIT and PDGFRA mutations in relation to the composite endpoint of relapse or death. Results: KIT and PDGFRA mutations were observed in 119 (53.8%) and 56 (25.3%) patients, respectively, whereas 46 (20.8%) patients had wild type (wt) disease. Univariable analyses showed that a high Miettinen risk category and the presence of ulceration and KIT deletions were associated with increased risk of relapse or death (p < 0.001; p = 0.0389 and p = 0.002, respectively). After adjusting for Miettinen risk score, KIT deletions remained an independent prognostic factor (HRadj = 2.65, 95% CI [1.15–6.13], p = 0.023). Moreover, KIT deletions in exon 11 codons 557, 558 or 559 were associated with a higher risk of relapse or death than wt tumors (HRadj = 3.29 95% CI [1.64–6.64], p = 0.001). Conclusions: KIT deletions in exon 11, especially those involving codons 557, 558 or 559, were correlated with a more aggressive gastric GIST phenotype and increased risk of relapse or death.